2011
DOI: 10.1089/jop.2010.0115
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Bimatoprost, Latanoprost, and Travoprost Under Simulated Daily Use

Abstract: Purpose: To determine the stability of bimatoprost, latanoprost, and travoprost under conditions of simulated daily use and varying degrees of thermal stress. Methods: Commercially available bimatoprost, latanoprost, and travoprost were obtained in their original bottles as distributed by the manufacturers. Bottles were stored in calibrated, nonhumidified, light-free incubators maintained at 278C, 378C, or 508C for 3, 9, 15, or 30 days. Capped bottles were inverted and left uncapped for 1 min daily to simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Other researchers have obtained similar measurements with commercial latanoprost (e.g. 57.7 ± 3.2 µg/mL) [20]. Latanoprost acid was detected in both release media and commercial latanoprost (0.037 ± 0.008 µg/mL and 1.03 µg/mL, respectively), but at concentrations that were far below those of latanoprost.…”
Section: Resultssupporting
confidence: 69%
“…Other researchers have obtained similar measurements with commercial latanoprost (e.g. 57.7 ± 3.2 µg/mL) [20]. Latanoprost acid was detected in both release media and commercial latanoprost (0.037 ± 0.008 µg/mL and 1.03 µg/mL, respectively), but at concentrations that were far below those of latanoprost.…”
Section: Resultssupporting
confidence: 69%
“…Several prostaglandin derivatives, including latanoprost, are reportedly susceptible to oxidation reactions, degraded into several oxidative products . Therefore, in order to decrease the contact of the labile derivative with the oxygen molecule, several kinds of oils and/or surfactants were employed, and the stabilizing effects were evaluated under stress conditions.…”
Section: Resultsmentioning
confidence: 79%
“…In a study done by Johnson et al, 12 to determine the concentration of bimatoprost, latanoprost, and travo-prost in conditions of simulated daily use and varying degree of thermal stress, medication bottles were stored in calibrated nonhumified, light-free incubators maintained at temperatures below and above the labeled indications for upto 30 days. They concluded that under all combinations of stress “off the shelf” bottles of these prostaglandin analogs showed mean bimatoprost concentration was 102% (100-116%) of the labeled concentration as compared to latanoprost which was 97 to 120% of the labeled concentration and travoprost was 83 to 143% of the labeled concentration.…”
Section: Discussionmentioning
confidence: 99%